Inovasi Pengembangan Teknologi Sistem Otomatis Pengendalian Hama di Kebun Buah Kelompok Tani Harapan Kota Palangka Raya - Arsana, Mu afa; Ngazizah, Febri Nur; Wilda, Robiatul Witari; Adi, Mika; Jipasca, Elon; Febrianto, Yahya; Alfanaar, Rokiy; Rahman, Sudarman; Suprayogi, Thathit; Citrariana, Shesanthi; Fatiqin, Awalul (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
The Community Service Program was carried out at the Harapan Farmers Group, Kereng Bangkirai Sub-district, Palangka Raya City, as an effort to provide innovative solutions to pest attack problems that often reduced fruit farm productivity. Previously, farmers had relied on manual pesticide spraying, which required considerable time, labor, and cost, and posed health risks. To address this challenge, the service team from the University of Palangka Raya developed an automated pest control system that was able to regulate pesticide spraying independently and efficiently. The activities were conducted through stages of socialization, training, and system mapping of automation in the fruit farm area, involving members of the farmers group actively. The implementation results showed an increase in participants’ understanding of the technology by 30–40 percent, improved efficiency in pesticide use by up to one-third compared to manual methods, and a reduction in working time by nearly 50 percent. This activity not only improved farmers’ skills and productivity but also served as a concrete step toward the implementation of sustainable smart farming in Palangka Raya through collaboration between the university and the community.